Perbandingan Personality Traits, Rasa Bersalah dan Rasa Malu Pengedar Narkoba: Nonresidivis Versus Residivis - Imaduddin Hamzah; Iman Santoso (Universitas Negeri Surabaya, 2021)
Various researches on drug abuse crimes have focused more on drug users or addicts. Meanwhile, investigations into drug dealers and producers have received very little attention. The majority of drug convicts in prisons are drug traffickers, which has resulted in a significant increase in drug trafficking cases in Indonesia. This study aimed to identify differences in personality traits, guilt, and shame of non-recidivists and drug dealers. The research was conducted on one hundred and fifty-five prisoners at the Cibinong Penitentiary, West Java, Indonesia. The measurement uses a scale of the big five personality traits which has been adapted into Indonesian, and the Guilt and Shame Proneness Scale (GASP) was developed by Cohen, Wolf, Panter, and Insko. This study found that there were differences in personality traits in terms of agreeableness and neuroticism between non-recidivists and recidivists. The difference test concluded that guilt and shame did not show any differences between the two groups of prisoners. This conclusion can provide a basis for consideration of developing a program to develop drug trafficking convicts to prevent the re-offense of crimes after being released.Keywords : Personality traits, guilt, shame, non-recidivists, recidivists Abstrak. Berbagai penelitian kejahatan penyalahgunaan narkoba selama ini lebih memfokuskan pada pengguna atau pecandu narkoba. Sedangkan penyelidikan terhadap para pengedar dan produsen narkoba masih sangat kurang mendapatkan perhatian. Mayoritas narapidana kejahatan narkoba di lembaga pemasyarakatan adalah para pengedar narkoba yang mengakibatkan peningkatan yang signifikan dalam kasus peredaran obat terlarang di Indonesia. Studi ini bertujuan mengidentifikasi perbedaan dalam sifat kepribadian, rasa bersalah, dan rasa malu nonresidivis dan residivis pengedar narkoba. Penelitian dilakukan pada seratus lima puluh lima narapidana di Lembaga Pemasyarakatan Cibinong, Jawa Barat, Indonesia, Pengukuran menggunakan skala the big five personality traits yang telah diadaptasi ke dalam bahasa Indonesia dan Guilt and Shame Proneness Scale (GASP) dikembangkan oleh Cohen, Wolf, Panter dan Insko. Studi ini menemukan ada perbedaan personality traits dalam aspek pada agreeableness dan neuroticism non-residivis dengan residivis. Uji perbedaan menyimpulkan rasa bersalah dan rasa malu tidak menunjukkan perbedaan antara kedua kelompok narapidana. Kesimpulan ini dapat memberikan dasar pertimbangan pembuatan program pembinaan narapidana pengedar narkoba untuk mencegah pengulangan kejahatan setelah bebas.